SQL Algorithm for Solving Markov Models by Graph Method - Pesko, Stefan (Communications - Scientific letters of the University of Zilina, 2003)
A simple graph algorithm for finding stabilized probabilities of the finite Markov models implemented in SQL is presented. The algorithm generates systematically all oriented spanning trees of a transition graph. The method is demonstrated on the computation of probabilities in the MMPP2/M/1/K queue.